Pengaruh Kualitas Produk, Harga, dan Kepercyaan Terhadap Keputusan Pembelian Pada Marketplace Shopee - Ekasari, Dhea; Putra, Pandi; Muslimin, Ulyana; Lukman, Siti Diva Syarifah (Jurnal Ilmiah Manajemen & Kewirausahaan, 2023)
This study aims to determine the effect of product quality, price and trust on purchasing decisions at the Shopee marketplace. This type of research is quantitative. The data source used is primary data and the sample in this study is the people of Parepare City who have made purchases at the Shopee marketplace. The data collection technique used was a questionnaire and the analysis technique used was multiple linear regression using SPSS version 23. The results of this study indicate that the Price and Trust variables partially affect the Purchasing Decision with a t-count value of Price of 5.034> 2.003 with a significant value of 0.000> 0.05 while the t-count value of Trust is 2.888> 2.003 with a significant value of 0.006 < 0.05 while the Product Quality variable has no partial effect with a t-count value of 1.057 < 2.003 with a significant value of 0.295> 0.05. The results of this study also show that there is a simultaneous influence on the variables of Product Quality, Price and Trust on Purchasing Decisions, where the F-count> F-table is 12.103> 2.77 with a significant value of 0.000 <0.05.